From entrepreneurial passion to business model innovation: The role of entrepreneurial learning and curiosity - Zou, Shuli (Frontiers in Psychology, 2022)
The impact of entrepreneurial passion on business model innovation has become a research focus in the field of entrepreneurship. This study aimed to examine the effect of entrepreneurial passion on entrepreneurial learning and business model innovation. The study used partial least square-structural equation modeling (PLS-SEM 4) to test the hypotheses on a sample of 389 manufacturing and technology enterprises in the South region of Henan province China. The results of this study revealed that entrepreneurial passion has a positive and significant influence on entrepreneurial learning and business model innovation. The findings of this study showed that entrepreneurial learning positively and significantly mediates the relationship between entrepreneurial passion and business model innovation. Furthermore, the results of this study indicated that curiosity positively and significantly moderates the relationship between entrepreneurial passion and entrepreneurial learning. Lastly, the results are discussed with implications and limitations, which open up future research perspectives.